2015
DOI: 10.1016/j.ijsu.2015.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium in elderly after elective and acute colorectal surgery: A prospective cohort study

Abstract: High incidence of delirium was found in both acute and elective colorectal surgery. Delirium was associated with adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
(18 reference statements)
2
26
2
2
Order By: Relevance
“…This makes it difficult to differentiate between delirium, dementia, depression or other reasons for agitation or sedation and does not reflect the real incidence of postoperative delirium in our population. Prospective measurement with validated scales in elective elderly surgical CRC patients reveals incidence rates of postoperative delirium of 11–31% . Comparable articles report variable rates of surgical site infections in older age groups, although the mean incidence is similar to our findings .…”
Section: Discussionsupporting
confidence: 83%
“…This makes it difficult to differentiate between delirium, dementia, depression or other reasons for agitation or sedation and does not reflect the real incidence of postoperative delirium in our population. Prospective measurement with validated scales in elective elderly surgical CRC patients reveals incidence rates of postoperative delirium of 11–31% . Comparable articles report variable rates of surgical site infections in older age groups, although the mean incidence is similar to our findings .…”
Section: Discussionsupporting
confidence: 83%
“…For example, there is no difference in the ICU stay between the delirium or non-delirium patients of abdominal disease, the possible reason for consideration is that the patients with abdominal diseases included in this study were all surgical patients and showed transient delirium, which reversal quickly and has no affection on ICU stay. It is in contrast to what has been demonstrated in Raats et al's study [37] which show that high incidence of delirium was found in abdominal surgery patients. Delirium was associated with adverse outcomes including higher hospital stay, mortality and discharge to a nursing home.…”
Section: Discussioncontrasting
confidence: 91%
“…However, surgeons have little knowledge of the assessment and management of preoperatively identifiable age-related factors that affect outcomes. Frailty, poor functional status, cognitive impairment and postoperative delirium in older people have all been shown to be associated with prolonged postoperative stay, adverse postoperative outcomes, [13][14][15][16][17] and postoperative discharge to a higher level of care. 18 The prevalence and severity of postoperative complications in an older surgical patient has also been shown to have a negative effect on the time take to return to baseline functional status.…”
Section: Preoperative Carementioning
confidence: 99%